An acoustofluidic device for efficient mixing over a wide range of flow rates. Issue 7 (27th February 2020) - Bachman, Hunter; Chen, Chuyi; Rufo, Joseph; Zhao, Shuaiguo; Yang, Shujie; Tian, Zhenhua; Nama, Nitesh; Huang, Po-Hsun; Huang, Tony Jun
Abstract : An acoustofluidic mixer which can achieve thorough mixing across a wide range of flow rates. Abstract : Whether reagents and samples need to be combined to achieve a desired reaction, or precise concentrations of solutions need to be mixed and delivered downstream, thorough mixing remains a critical step in many microfluidics-based biological and chemical assays and analyses. To achieve complete mixing of fluids in microfluidic devices, researchers have utilized novel channel designs or active intervention to facilitate mass transport and exchange of fluids. However, many of these solutions have a major limitation: their design inherently limits their operational throughput; that is, different designs work at specific flow rates, whether that be low or high ranges, but have difficulties outside of their tailored design regimes. In this work, we present an acoustofluidic mixer that is capable of achieving efficient, thorough mixing across a broad range of flow rates (20–2000 μL min −1 ) using a single device. Our mixer combines active acoustofluidic mixing, which is responsible for mixing fluids at lower flow rates, with passive hydrodynamic mixing, which accounts for mixing fluids at higher flow rates. The mechanism, functionality, and performance of our acoustofluidic device are both numerically and experimentally validated. Additionally, the real-world potential of our device is demonstrated by synthesizing polymeric nanoparticles with comparable sizes over a two-order-of-magnitude wide range of flow rates. This device can be valuable in many biochemical, biological, and biomedical applications. For example, using our platform, one may synthesize nanoparticles/nanomaterials at lower flow rates to first identify optimal synthesis conditions without having to waste significant amounts of reagents, and then increase the flow rate to perform high-throughput synthesis using the optimal conditions, all using the same single device and maintaining performance.